2007
DOI: 10.1266/ggs.82.135
|View full text |Cite
|
Sign up to set email alerts
|

The genome size evolution of medaka (Oryzias latipes) and fugu (Takifugu rubripes)

Abstract: Evolution of the genome size in eukaryotes is often affected by changes in the noncoding sequences, for which insertions and deletions (indels) of small nucleotide sequences and amplification of repetitive elements are considered responsible. In this study, we compared the genomic DNA sequences of two kinds of fish, medaka (Oryzias latipes) and fugu (Takifugu rubripes), which show two-fold difference in the genome size (800 Mb vs. 400 Mb). We selected a contiguous DNA sequence of 790 kb from the medaka chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
(43 reference statements)
4
10
1
Order By: Relevance
“…An explanation for this may be found in the evolution of genome size. It has been shown that teleost genomes tend to accumulate most indels in intergenic or intronic regions leading towards large differences in genome size, while synteny of genes is conserved [47]. Thus one may conclude that the ratio of the maxima in the insert size distributions of BAC-clones equals the ratio of genome sizes.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for this may be found in the evolution of genome size. It has been shown that teleost genomes tend to accumulate most indels in intergenic or intronic regions leading towards large differences in genome size, while synteny of genes is conserved [47]. Thus one may conclude that the ratio of the maxima in the insert size distributions of BAC-clones equals the ratio of genome sizes.…”
Section: Discussionmentioning
confidence: 99%
“…They have a lower percentage of repeated sequences (especially DNA transposons) and shorter intronic sequences. This situation would depend both on a high rate of intron and transposon loss and on a higher level of indels (insertions/ deletions) [Imai et al, 2007;Loh et al, 2008;Noleto et al, 2009;Guo et al, 2012].…”
Section: Deuterostomesmentioning
confidence: 99%
“…In addition, teleost and tetrapod genomes are known to have markedly different transposable elements (TEs); teleost genome contains thousands of copies of several types of retrotransposon that are not present in tetrapod (Aparicio et al 2002). Such TEs are estimated to be responsible for more than 50% of genome-size difference between pufferfishes and medaka (Imai et al 2007). The proliferation and insertion of the TE into new genomic sites is implied to played a role in the evolution of brain development in mammals (Sasaki et al 2008).…”
Section: Genome Evolutionmentioning
confidence: 99%